Penguatan Strategi Branding Awarness Untuk Peningkatan Jumlah Konsumen Pada Cafe ‘Saat Kopi’ Surabaya - Yusup; Rachmanto, Nanang; Fajar Suryani, Indah (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The first café emerged from western countries. The term café, most commonly found in France, was then adopted by cities in England at the end of the 19th century. The term Café comes from Coffee which means coffee. Café is a suitable place to relax, relieve fatigue, as well as a place to meet relatives and work partners. In this era of globalization and increasingly tight competition in the business world, business actors, especially cafes, are encouraged to be able to transform, adapt and compete well, one of which is by increasing brand awareness. Brand awareness is considered important by cafe owners so that customers can associate the products and services owned by the cafe every time they make a transaction or visit the cafe 'Saat Kopi' Surabaya. The aim of this service is to increase the brand awareness of the 'Saat Kopi' cafe through a promotional approach connected to social media with an attractive form and the friendliness of employees who are still young and have potential to achieve the set business goals. With the method of implementing this service activity in the form of education, mentoring and a predetermined strategy, it is hoped that it will have an impact on increasing the number of visitors as well as sales of beverage and snack products at the 'Saat Kopi' café in Surabaya.